Enhancement of Fibroblast Proliferation, Vascularization and Collagen Synthesis in the Healing Process of Third-Degree Burn Wounds by Topical Arnebia euchroma, a Herbal Medicine: - Ashkani-Esfahani, Soheil; Imanieh, Mohammad Hossein; Khoshneviszadeh, Mahsima; Meshksar, Aidin; Noorafshan, Ali; Geramizadeh, Bita; Ebrahimi, Sedigheh; Handjani, Farhad; Nadimi, Elham; Seyed Jafari, Seyed Morteza (Galen Medical Journal, 2013)
Introduction: The present study was conducted to evaluate the wound healing effect of Arnebia euchroma (AE) extract, which is traditionally used in some Indian, Chinese, and Iranian tribes, on histomorphometrical parameters involved in the healing process of third-degree burn wounds by using stereological analyses. Methods and Materials: In an experimental study, 48 female Sprague-Dawley rats, each with a standard third-degree burn wound on the posterior surface of the neck, were divided into four groups; AE10 and AE20 groups were treated with carboxymethylcellulose (CMC) gels which contained AE hydroalcoholic extract at the concentration of 10% and 20%, respectively; the untreated burned (UB) group, which received no treatment; and the gel-base treated group. Wound closure rate, fibroblast proliferation, volume density of collagen bundles, length density, and mean diameter of the vessels were measured. Results: Wound closure rate, fibroblast population, volume density of collagen bundles, and length density of vessels were significantly improved by AE10 and AE20 in comparison with the gel-base and UB groups (P value <0.05). Conclusion: Although previous investigations on the different aspects of the wound healing effects of AE and the results of this study exhibited the positive effects of topical Arnebia euchroma on third-degree burn wound, introducing AE as an alternative wound healing agent requires more investigations on its efficacy on human, safety, and possible adverse effects.[GMJ. 2012;1(2):53-59]